CLINICAL CHARACTERISTICS AND CAUSES OF SMALL SCALE DISORDER MOTOR SKILLS IN CHRONIC CEREBRAL ISCHEMIA - Yo’ldosheva Naima Qudratovna (Лучшие интеллектуальные исследования, 2024)
Annotation: Vascular brain lesions are the most common cause of death in many countries of the world. Stroke ranks second in the structure of total mortality in Russia. More than 400 thousand cases of strokes are registered annually, with a mortality rate of up to 35%. The primary disability rate after a stroke is 3.2 per 10% of the population, and no more than 20% of those who previously worked return to work. People with disabilities due to cerebrovascular diseases account for 9.8% of the total contingent of people with disabilities among the population. Statistical data indicate that the increase in vascular diseases of the brain occurs due to an increase in the prevalence of chronic cerebral ischemia (CHEM).